Recent improvements in various renewable energies and their effects on the environment and economy: A review article - Kanca, Muhammed Sait; Qader, Ibrahim Nazem; Qadir, Mohammed Nadhim; Kok, Mediha (TUBITAK, 2021)
The increasing populations and expanding industries all over the world led to enhance the need for energy. Since most of the nowadays energies are generated by fossil fuels, so the ratio of greenhouse gases like CO2 extremely increased that impacted the environment and other sectors. In this study, the renewable energies used globally and in Turkey have been described. Also, the different fields of studies, which covered by different researchers have been highlighted. Besides, the opportunity and the corresponding advantages that can be achieved by harnessing renewable energies have been determined. Consequently, there is good progress in development, and investments have been made in this area, especially by governments, international organizations, and highly advanced and large private companies. Finally, this article provides a detailed review by collecting and examining a variety of renewable energy sources and highlighting prospects for scientists and investors. © 2021, TUBITAK. All rights reserved.
Yenilenebilir enerjilerde son gelişmeler ve çevre ve ekonomi üzerindeki etkileri: Derleme makale
Keywords: Economy; Efficiency; Renewable energies